Analisis kesulitan belajar matematika dalam menyelesaikan soal cerita materi operasi hitung bilangan cacah kelas IV SD Negeri Jajar Surakarta tahun ajaran 2024/2025 - Farrasa Nabiila; Jenny Indrastoeti Siti Poerwanti; Riyadi Riyadi (Didaktika Dwija Indria, 2026)
This study aims to describe students' mathematical learning difficulties in solving word problems involving arithmetic operations on whole numbers based on Polya’s problem- solving framework. The research was conducted at SD Negeri Jajar Surakarta using a descriptive qualitative approach. Subjects involved in this research were selected from students in class IV of the 2024/2025 academic year through purposive sampling. Data were collected through tests and interviews, analyzed using the Miles and Huberman technique, and processed through a triangulation of time and technique to ensure their validity. The results show that students encountered challenges in all of Polya’s methods. Students struggled to read carefully and note the significant information in understanding the problem. In devising a plan, students faced difficulties in identifying problem types and translating certain words, such as “Each,” “Dozen,” and “Gross.”. Students had difficulties in sequential calculations and were unable to master basic multiplication and division while carrying out the plan. In the final step, students were incapable of evaluating the results or pointing out alternative methods to solve the problem.